Prevalence and antimicrobial susceptibility of Salmonella enterica Typhi in febrile patients: a cross-sectional study - Khattak, Zainab; Aala, Roohul; Sani, Nimra; Khan, Sher A; Khan, Sana; Shah, Syed A; Ansar, Rubina; Riaz, Mohsin; Ahmed, Hasnat (The Journal of Infection in Developing Countries, 2025)
Introduction: Typhoid fever, caused by Salmonella Typhi, is a serious health problem, especially in developing countries like Pakistan where antibiotics are usually prescribed without susceptibility testing or epidemiological surveillance. Consequently, antibiotic-resistant typhoid bacteria appear, but are not reported to the authorities. There is limited research on the prevalence and antibiotic susceptibility patterns of S. Typhi among febrile patients in Swabi, Pakistan. This study aimed to address this gap at the Bacha Khan Medical Complex in Swabi. Methodology: Laboratory records of hospitalized patients who received a blood culture from September 2022 to August 2023 were reviewed in this retrospective, cross-sectional study. Every isolate of S. Typhi underwent antibiotic susceptibility test using modified Kirby-Bauer disk diffusion and agar-dilution methods to measure the isolates' minimum inhibitory concentration (MIC) for ciprofloxacin and azithromycin. The data were analyzed using SPSS version 24.0. Results: 4.85% of febrile patients were positive for S. Typhi, with a higher prevalence in the 0–14 years age group. Male gender and seasonal variation were significant factors. The isolates were resistant to ampicillin, amoxicillin, cefotaxime, and ciprofloxacin; and sensitive to azithromycin, and carbapenems. The MICs for ciprofloxacin were between 0.06 to 16 µg/mL. Among the isolates, 1.094% were sensitive and 98.90% were resistant to ciprofloxacin; and 100% isolates were susceptible to azithromycin. Conclusions: Azithromycin and carbapenem were a suitable empirical therapy choice. However, the isolates were highly resistant to conventional first-line antibiotics (ampicillin, amoxicillin), second generation fluoroquinolones (ciprofloxacin), and third-generation cephalosporins (ceftriaxone, cefotaxime), that are considered vital in typhoid treatment.